Comparação entre suturas contínua e interrompida, para anastomose vesicouretral após prostatavesiculectomia radical retropúbica - Denny Fabricio Magalhaes Veloso (2012)
The vesicourethral reconstruction in retropubic prostatectomy (RP) is commonly done with interrupted suture. Running suture can be used in perineal or laparoscopic access. The vesicourethral anastomosis technique affect urinary complication incidence, which are different according to the surgical approach. The aim of this work was to compare results of urinary continence and bladder neck contracture after RP, between two techniques of vesicourethral anastomosis. Method: 50 patients who underwent RP, were allocated into two groups randomly and prospectively, according to the technique for vesicourethral anastomosis: Group 1 (n = 25) running suture; Group 2 (n = 25) six interrupted sutures. The patients ages were 63 ± 9 years in Group 1 and 63 ± 7 years in Group 2. The time for anastomosis was recorded. Urinary continence and bladder neck contracture were assessed after removal of bladder catheter and two, four and six months after surgery. They answered a questionnaire regarding their own symptoms of lower urinary tract at these time points. Those who had not any urinary leakage amount were classified as continents. Cystoscopies were performed in patients with symptoms of bladder outlet obstruction in order to confirm bladder neck contracture. The Students t-test and Fishers exact test were used so as to compare the results between groups. The level of significance was 5% (p <0.05). Results: the respective percentages of urinary continence, immediately after removing the Foley catheter and two, four and six months after surgery were 36%, 56%, 68% and 80% in Group 1 and 20%, 28%, 36% and 48% in Group 2. Differences between groups were significant at two months (p = 0.044), four months (p = 0.023) and six months (p = 0.018). Bladder neck contracture was detected in only three patients in Group 2. Has taken longer time to running suture (17.40 ± 4.26 minutes) over interrupted suture (12,20 ± 3,09 minutes), with significant difference (p = 0.0001). Conclusion: even though has taken longer time for vesicourethral anastomosis, the running suture had better urinary continence after surgery, compared to the interrupted suture.